Coral Infanto-Juvenil: Projeto Social ou Trabalho? - Orasmus, Carla Caroline Dums (2015)
This study deals with children and adolescents who are in situations of social vulnerability, many of them institutionalized. The objective of this research is to analyze the participation of children and adolescents in an institutional artistic presentation, characterized as social work, is configured in child labor. The extent of this project refers to training courses offered by the applicant and health care institution. There was an investigation by the Ministry of Labour to check child labor exploitation clues. The qualitative research was conducted during the months of December 2014 to January 2015. We opted for the content analysis, from directed observation, semi-structured interviews and rescue news. Other buildings identified by the survey show that some actions taken by the bank show evidence of social project, such as the health plan offer for all institutionalized of the host institutions participating in the choir, as well as tutoring. However, there is still long way to go to the bank to use up the naming social project.